THE POSITION OF THE PROSECUTORS OFFICE OF UZBEKISTAN AND TURKEY IN THE SYSTEM OF STATE STATUS - Khudoberdievich, Abduolimov Urinboy (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
General Background: The role of prosecutor's offices is pivotal in maintaining the rule of law and upholding justice within the framework of state power. Specific Background: This article examines the distinct functions and structures of the prosecutor's offices in Turkey and Uzbekistan, highlighting their contributions to the legal system and governance in both countries. Knowledge Gap: Despite the importance of these institutions, there is a lack of comparative legal studies that explore their operational differences and similarities, particularly between Turkey and Uzbekistan. Aims: This study aims to provide a comprehensive legal analysis of the prosecutor's offices in both nations while identifying best practices from Turkey that could be adapted to enhance the effectiveness of Uzbekistan's prosecutorial system. Results: The findings reveal significant structural and functional differences between the two countries' prosecutor's offices, particularly in their approach to accountability, oversight, and public engagement. Additionally, the study identifies several best practices from Turkey that could improve the efficiency and transparency of Uzbekistan's prosecutor's office. Novelty: This research contributes to the field by offering a unique comparative perspective on the prosecutor's offices of Turkey and Uzbekistan, emphasizing practical reform strategies. Implications: The insights gained from this analysis have significant implications for policymakers and legal practitioners in Uzbekistan, suggesting that the adaptation of successful Turkish practices could lead to a more robust and accountable prosecutorial framework, ultimately strengthening the rule of law and public trust in the justice system.